The role of parents and related factors on adolescent computer use - Jennifer A. Epstein (SAGE Publishing, 2012)
Background. Research suggested the importance of parents on their adolescents' computer activity. Spending too much time on the computer for recreational purposes in particular has been found to be related to areas of public health concern in children/adolescents, including obesity and substance use. Design and Methods. The goal of the research was to determine the association between recreational computer use and potentially linked factors (parental monitoring, social influences to use computers including parents, age of first computer use, self-control, and particular internet activities). Participants (aged 13-17 years and residing in the United States) were recruited via the Internet to complete an anonymous survey online using a survey tool. The target sample of 200 participants who completed the survey was achieved. The sample's average age was 16 and was 63% girls. Results. A set of regressions with recreational computer use as dependent variables were run. Conclusions. Less parental monitoring, younger age at first computer use, listening or downloading music from the internet more frequently, using the internet for educational purposes less frequently, and parent's use of the computer for pleasure was related to spending a greater percentage of time on non-school computer use. These findings suggest the importance of parental monitoring and parental computer use on their children's own computer use, and the influence of some internet activities on adolescent computer use. Finally, programs aimed at parents to help them increase the age when their children start using computers and learn how to place limits on recreational computer use are needed.